2017
DOI: 10.1002/jbm.b.33846
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of fluorine‐containing bioactive glass nanoparticles synthesized by sol–gel route assisted by ultrasound energy

Abstract: In the last decades, studies about the specific effects of bioactive glass on remineralization of dentin were the focus of attention, due to their excellent regenerative properties in mineralized tissues. The incorporation of Fluorine in bioactive glass nanoparticles may result in the formation of fluorapatite (FAP), which is chemically more stable than hydroxyapatite or carbonated hydroxyapatite, and therefore is of interest for dental applications. The aim of this study was to synthesize and characterize a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…It was already reported that these defects can display a negative influence on the corrosion resistance of magnesium in physiological media [46]. Thus, in practice, the particle size of BG could be decreased by, for example, either ball-milling or the use of a different sol-gel route [47].…”
Section: Discussionmentioning
confidence: 99%
“…It was already reported that these defects can display a negative influence on the corrosion resistance of magnesium in physiological media [46]. Thus, in practice, the particle size of BG could be decreased by, for example, either ball-milling or the use of a different sol-gel route [47].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, undiluted cement significantly inhibited the migration and proliferation of hDPSCs [ 60 ]. Furthermore, notable research trends included the predominant use of these materials for addressing dentine hypersensitivity [ 61 , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] ] or promoting dentine regeneration [ 65 , 141 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sphericity of bioactive glass particles is an important feature for dental applications, such as in the treatment of dentin hypersensitivity, since the irregular morphology could cause micro-cuts and micro-injuries at the implant site, increasing the healing time 2,8,14 . Moreover, the cell adhesion and proliferation in materials with spherical morphology are greater when compared to materials with irregular morphology since there will not be a physical barrier to prevent their movement 22 .…”
Section: Morphological Analysismentioning
confidence: 99%
“…From the 5th day it is possible to identify a peak related to sodium chloride (JCPDS 5-0628), that may have precipitated from the SBF solution, once this solution has a high concentration of Na + and Clions. After 28 days of immersion, samples BGFM and BGFU presented peaks related to carbonated hydroxyapatite and / or fluorapatite (JCPDS 31-267), however the distinction of the two phases is hampered by the isomorphic property of these two minerals, so their peaks would be overlapping 2,44 . Al-Noaman and co-workers showed that CaF 2 have an influence on bioactivity of the glasses, but are not incompatible with osteoblast-like cell viability because the cells were able to grow and proliferate on the glass surface, thus this implies that CaF 2 enriched glass may be useful for stimulating osteoblastic growth and bone formation in vivo 45 .…”
Section: Preliminary In Vitro Bioactivity Study -Sbf Assaymentioning
confidence: 99%